Role of Artificial Intelligence in the Social Relations in the Digital Era - Parul; Rakesh Verma; Pooja Shekhawat; Taruna (International Journal of Indian Psychȯlogy, 2025)
Nowadays technology is evolving at a faster pace. The current currency is Artificial Intelligence. In short, Artificial intelligence (AI) is refers to a computer-based system capable of performing cognitive and intricate tasks that historically only a human could do, such as reasoning, making decisions, or solving problems. In the digital world the ubiquitous presence of AI has altered the human life and has wider applications in industry, automation, transportation, communication, education, health and so on. The present article deals with the role of artificial intelligence in the facilitation of social relations such as friendship, marriage, dating, romantic love etc. It is observed that AI has significant benefits to the formation of social relations. Additionally, the present article also emphasized the limitations, risks, challenges and ethical issues.